ANALYSIS OF CHRITICAL THINKING SKILL OF STUDENTS ON THE CONCEPT OF ‎HUMAN MOVEMENT SYSTEM USING CONCEPT MAP - nengsih juanengsih; dhuhana putri ramadhani; yuke mardiati (EDUSAINS, 2017)
Critical thinking are capability that need to analyzing, making decisions,  solving problems and making arguments. This study aims to find out critical thinking skills used concept map on human skeletal and muscular system concept. The research was conducted in State Senior High School 2 of South Tangerang City. The method used was descriptive research. The sampling was done by purposive sampling technic, and the action class was randomly determined by the teacher. The sample were 29 students. The instrument used were the concept map and interview sheet which have been tested for the validity and the reliability.  The data were analyzed by descriptive quantitative and qualitative statistic. The result shows that critical thingking skills used concept map was low-sore on average 31.95%. Concept Map can used for measure critical thinking skills especially on analysis and synthesis. Critical thingking skills used concept map indicator include two indicator, such as  analysis 34.3 %, synthesis 29.08%. Keywords : Critical Thingking skills; concept map; human skeletal and muscular system